2020
DOI: 10.3390/plants9121772
|View full text |Cite
|
Sign up to set email alerts
|

Induction, Multiplication, and Evaluation of Antioxidant Activity of Polyalthia bullata Callus, a Woody Medicinal Plant

Abstract: Polyalthia bullata is an endangered medicinal plant species. Hence, establishment of P. bullata callus culture is hoped to assist in mass production of secondary metabolites. Leaf and midrib were explants for callus induction. Both of them were cultured on Murashige and Skoog (MS) and Woody Plant Medium (WPM) containing different types and concentrations of auxins (2,4-dichlorophenoxyacetic acid (2,4-D), α-naphthaleneacetic acid (NAA), picloram, and dicamba). The callus produced was further multiplied on MS an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 68 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…44 7 carbon resonance signals at δ C 110.56, 120.56, 140.38, 146.59 and 169.47 were in agreement with 3,4,5-trihydroxybenzoic acid. 22 These carbon resonance signals revealed that compound 1 contained two structural units dihydromyricetin and 3,4,5-trihydroxybenzoic acid. To assign the relative configurations of compound 1 , the ROESY correlations between H-1/H-2′, H-1/H-6′, H-2/H-2′ and H-2/H-6′ were done; it indicated that H-1, H-2 H-2′, and H-6′ were cofacial (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…44 7 carbon resonance signals at δ C 110.56, 120.56, 140.38, 146.59 and 169.47 were in agreement with 3,4,5-trihydroxybenzoic acid. 22 These carbon resonance signals revealed that compound 1 contained two structural units dihydromyricetin and 3,4,5-trihydroxybenzoic acid. To assign the relative configurations of compound 1 , the ROESY correlations between H-1/H-2′, H-1/H-6′, H-2/H-2′ and H-2/H-6′ were done; it indicated that H-1, H-2 H-2′, and H-6′ were cofacial (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, the callus culture could be a realistic source of bioactive secondary metabolites production with no time and space limitation and the technique has been widely used as an alternative for the production of plant secondary metabolites. 22 Therefore, the current research was designed to establish the in vitro callus cultures of this species as an alternative bioactivity-based reproducible approach for extraction and isolation of key bioactive compounds. Further, we assessed the cytotoxicity and antibacterial potential of the callus extract on A549, 4T1 and NCI-H1975 and against a panel of Gram positive bacteria and Gram negative bacterial pathogens, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Many fields can use this approach, which allows the production of high-value bioactive compounds such as pharmaceuticals, food, and cosmetics [151]. The quantity and quality of the obtained metabolites can be greatly influenced by various parameters such as the nature of the elicitor, its concentration, and the exposure time, Table 4 [152][153][154][155][156][157][158].…”
Section: Elicitation Of In Vitro Productsmentioning
confidence: 99%
“…The study of medicinal and aromatic plants identified by the authors will be carried out according to a selection of the most used species, based on the country or area where the research is being conducted [ 4 ]. As such, in this special edition, the authors will be able to demonstrate their scientific contributions through the botanical description of medicinal plants—both traditionally and currently used species—as well as the chemical characterization of their respective phytocomplexes and their proven pharmacological action [ 5 , 6 ].…”
mentioning
confidence: 99%